A comprehensive review of the genetic and biological evidence supports a role for MicroRNA‐137 in the etiology of schizophrenia. Issue 2 (14th June 2017) - Sakamoto, Kensuke; Crowley, James J.
Abstract : Since it was first associated with schizophrenia (SCZ) in a 2011 genome‐wide association study (GWAS), there have been over 100 publications focused on MIR137, the gene encoding microRNA‐137. These studies have examined everything from its fundamental role in the development of mice, flies, and fish to the intriguing enrichment of its target gene network in SCZ. Indeed, much of the excitement surrounding MIR137 is due to the distinct possibility that it could regulate a gene network involved in SCZ etiology, a disease which we now recognize is highly polygenic. Here we comprehensively review, to the best of our ability, all published genetic and biological evidence that could support or refute a role for MIR137 in the etiology of SCZ. Through a careful consideration of the literature, we conclude that the data gathered to date continues to strongly support the involvement of MIR137 and its target gene network in neuropsychiatric traits, including SCZ risk. There remain, however, more unanswered than answered questions regarding the mechanisms linking MIR137 genetic variation with behavior. These questions need answers before we can determine whether there are opportunities for diagnostic or therapeutic interventions based on MIR137 . We conclude with a number of suggestions for future research on MIR137 that could help to provide answers and hope for a greater understanding of this devastating disorder.